2019
DOI: 10.33225/jbse/19.18.300
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Difficulties Pre-Service Primary Teachers Have With Static Electricity

Abstract: Static electricity is the introductory chapter to electricity in all high school and university Physics textbooks. The interpretations of static electricity phenomena are not obvious, even in higher education. This research was conducted to identify the major difficulties which pre-service primary teachers encounter in explaining static electricity. They conducted electrostatic experiments focused on different types of electricity, in the context of an Introductory Physics Laboratory Course. The data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…It was also observed that these teacher candidates had difficulty associating the atomic structure in electrification with touch and friction. These findings are consistent with the results of the research reported in the literature (Tezcan & Salmaz, 2005;Sarıkaya, 2007;Stefanidou and et al, 2019). It was also observed that the teacher candidates could not attribute their knowledge about the atom to their explanations about electrification by friction and touch.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was also observed that these teacher candidates had difficulty associating the atomic structure in electrification with touch and friction. These findings are consistent with the results of the research reported in the literature (Tezcan & Salmaz, 2005;Sarıkaya, 2007;Stefanidou and et al, 2019). It was also observed that the teacher candidates could not attribute their knowledge about the atom to their explanations about electrification by friction and touch.…”
Section: Discussionsupporting
confidence: 91%
“…This may be evidence that students contribute little to their focus on macroscopic phenomena and their understanding of microscopic procedures. It is also similar to the conclusion presented in the relevant literature (Voutsina & Ravanis, 2011;Dederberg, 2012;Cheng, 2015;Stefanidou et al, 2019) and introduces the electrical curriculum with basic electrical phenomena (electrification by friction, contact, and induction) and microscopic methods to improve students' understanding It is suggested that they should focus on explanatory models.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Because of that matter, some researches had been held to provide information about student understanding, especially in learning science concepts. The different insight of student concepts had been defined by a number of terms like "alternative conceptions" (Wandersee et al, 1994), "conceptual difficulties" (Stefanidou et al, 2019), "misconceptions " (Eshach et al, 2018), "mental models" (Wuellner et al, 2017), and others.…”
Section: Introductionmentioning
confidence: 99%
“…Electrodynamic and electrostatic abstract concepts require some good intuitive and analytical capabilities to be visualized with multiple assistive media (Campos et al, 2019). The discovery of students at the university level in Athens has difficulty describing and analyzing electrostatic vectors of force (Stefanidou. et al, 2019).…”
Section: Introductionmentioning
confidence: 99%